CORRELATION OF HBA1C LEVELS AND HEALING RATE OF LOWER EXTREMITY INFECTION IN PATIENTS WITH DIABETES: A RETROSPECTIVE STUDY - Danga, Justiene Mia Klarisse; Adorable-Wagan, Perie (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Despite better knowledge of complications of lower extremity infection and efforts to improve prevention of foot ulcers; there has been no established level of HbA1c identified in treatment of lower extremity infection in diabetes. METHODOLOGY Retrospective cohort study of 74 patients admitted from 2013 to 2016 for which electronic data were retrieved from the Records section and Wound Care Center of The Medical City. Parameters such as HBA1C, wound size, University of Texas Classification, length of hospital stay and follow up were documented to establish outcome of the study. RESULTS 49% of patients have HbA1c of 8.0% and above, with hospital stay of less than 8 days (64%), had antibiotics for less than 15 days (53%), had wound debridement (67%), and experienced wound healing for 14 days or less. Fisher’s Exact Test at 5% level of significance showed that HbA1c is significantly correlated with the mean duration of healing, duration of antibiotics and wound debridement. HbA1c of 8.0% and higher presents a higher risk of longer antibiotic use (odds ratio 3.99), higher risk of wound debridement (hazard ratio 5.60) and longer healing time (hazard ratio 2.0). CONCLUSION Patients with HBA1c of more than 8.0% had prolonged healing time, higher risk to undergo wound debridement and longer duration of antibiotics. We highly recommend a strict level of glycemic control specifically to populations who are at risk to develop lower extremity infections such as those with peripheral artery disease and with previous history of lower extremity infection.